The Effect of Court Angles Strategy (Educational Corners) On Learning and Retaining Forehand in Tennis for Students - AL-Rammahi, Aaya; Sattar , Hasnaa (Journal of Physical Education, 2022)
The research aimed at identifying the effect of using court angles strategy (educational corners) on learning and retaining forehand shot in lawn tennis. The researchers used the experimental method on (235) third year college of physical education and sport sciences students. The subjects were (15) controlling group and (15) experimental group. The training program was applied for eight weeks with one teaching session per week. The researchers concluded that teaching sessions have a significant effect learning and retaining on forehand shot.